Ecological niche differentiation in peripheral populations: a comparative analysis of eleven Mediterranean plant species. Issue 10 (13th March 2018) - Papuga, G.; Gauthier, P.; Pons, V.; Farris, E.; Thompson, J. D.
Abstract : The 'central‐peripheral' hypothesis has provided a baseline for many studies of population dynamics and genetic variability at species distribution limits. Although peripheral populations are often assumed to occur in ecologically marginal conditions, little is known about whether they effectively occur in a distinct ecological niche. A cross‐taxa analysis of 11 Mediterranean vascular plants were studied. We quantified variation in the ecological niche between populations at the northern range limits of species in Mediterranean France and those in the central part of the distribution in continental Spain or Italy in 2013–2014. We analyzed both the macro‐ecological niche where populations occur in terms of broad habitat and altitudinal range and the micro‐ecological niche where individual plants grow in terms of soil and structural biotic and abiotic characteristics. Most species occur in a single broad habitat type common to central and peripheral populations and have a narrower altitudinal range in the latter. In contrast, for the micro‐ecological niche we detected marked variation in several niche parameters among central and peripheral populations. Although many differences are species‐specific some are common to several species. We found a trend towards narrower micro‐niche breadth in peripheral populations. Our results illustrate the importance of studying the precise ecological characteristics where plants grow and the pertinence of a multi‐species approach to correctly assess niche variation. The ecological originality of peripheral populations underlines their evolutionary potential and conservation significance.